EFFECT OF SKIN FAT ON CAPSAICIN TRANSFERSOME GEL: IN VITRO PENETRATION STUDIES USING FRANZ DIFFUSION CELLS - ISKANDARSYAH; ADELIA, SAORI SALMA; APRIANTI, INDAH (International Journal of Applied Pharmaceutics, 2023)
Objective: Capsaicin is a highly lipophilic substance that generally uses an organic cosolvent added to diffusion medium in penetration tests to increase penetration by fluidizing fat. This study aims to determine the effect of subcutaneous fat on the penetration of capsaicin as lipophilic substances formulated into transfersome and compare it to hydrophilic substances, namely vitamin C. Methods: The thin layer method was used to develop the transfersome formulation using Phospholipon 90G and Tween 80. Vesicle size, zeta potential, deformability index, morphology, and entrapment efficiency were all characterized. The transfersome suspension was then developed into a gel formulation using 1% carbomer. The in vitro penetration test was performed using a Franz diffusion cell of rat skin with and without subcutaneous fat. Results: The cumulative amount of penetration on fat-free membranes compared to membranes with fat for capsaicin transfersome gel 920.28±3.42 μg/cm2 and 762.22±1.73 μg/cm2, respectively, then for non-transfersome capsaicin gel was 833.33±0.84 μg/cm2 and 595.80±0.32 μg/cm2 respectively, and for vitamin C non-transfer some gel 776.45±1.19 μg/cm2 and 654.69±3.36 μg/cm2 respectively. Conclusion: According to these results, it can be concluded that the presence of subcutaneous fat affects inhibiting the penetration of lipophilic substances.